Dilema in Managing Children Born with Antenatally Detected Ureteropelvic Junction Obstruction (UPJO) (Bangladesh Journal of Child Health, 2024)
Now-a-Days, attitudes of paediatric urologists have been changed from surgical to observational regarding definite management of congenital ureteropelvic junction obstruction (UPJO), because many cases of UPJO goes away on its own before baby is born. In the last decade, this type of management trend has become progressively increased despite the lack of precise predictors of outcome. But these patients should be brought into regular follow-up by physical examinations, ultrasonography and nuclear imaging to observe resolution events. In some clinical scenario surgical intervention is inevitable such as solitary kidney or child with infection. Now-a-days, it is a good practice by the modern pediatric urologists frequently consults with the guardians about advantage and disadvantage of observational and surgical management of antenatally detected hydronephrosis due to UPJO of their babies and their future outcome. As a result guardians feel comfortable in decision making.Bangladesh J Child Health 2022; Vol 47 (2) : 54-58